Potato: Breeding and Genomics - Luthra, Satish K.; Kumar, Vinod; Tiwari, Jagesh K. (Vegetable Science, 2023)
The commonly cultivated potato is a tetraploid and belongs to the species Solanum tuberosum, which includes two subspecies viz. ssp. tuberosum adapted to long days and ssp. Andigena adapted to short days. The conventional potato breeding programmes depend mainly on the identification of promising parental lines for making desired crosses, the creation of genetic variability through the crossing and subsequently the selection of desirable recombinants for further evaluation and vegetative propagation. During the last seven decades, ICAR-CPRI has developed and released as many as 69 improved varieties and one TPS population. These varieties cater to the need of the farmers across the country; and have superior agronomic attributes and resistance to different biotic and abiotic stresses. The somatic hybrids has been produced successfully by utilization of wild solanum species like S. etuberosum, S cardiophyllam and S pinnetisectum. Further, considerable work has been done in potato applying molecular biology and genomics approaches to address biotic and abiotic stress and quality traits